Photoluminescence wavelength from stacking fault with complicated structure in 4H-SiC epitaxial layer. (1st October 2022) - Suo, Hiromasa; Yamashita, Tamotsu; Eto, Kazuma; Miyasaka, Akira; Osawa, Hiroshi; Kato, Tomohisa; Okumura, Hajime
Abstract: We investigated the photoluminescence wavelength emitted at room temperature from novel stacking faults with a complicated stacking sequence in the epitaxial layer on p-type 4H-SiC substrate. From analysis of photoluminescence imaging and synchrotron X-ray topography, we consider that these complicated stacking faults originate from p-type substrates. We investigated the relationship between photoluminescence energy and stacking sequence of various stacking faults, and confirmed that the maximum number of layers in complicated stacking faults determines the photoluminescence emission energy. This relationship, which was previously only reported for 3C-type stacking faults, follows simple quantum-well theory. We extended this theory to stacking faults with complex structures, focusing on the maximum number of layers.